Optimization of heat transfer properties of nanofluid flow over a shrinking surface through mathematical modeling - Pannala, R. K. Pavan Kumar; Bhandari, Anupam (Zielona Góra: Uniwersytet Zielonogórski)
In the current study, a three dimensional incompressible magnetohydrodynamic (MHD) nanofluid flow over a shrinking surface with associated thermal buoyancy, thermal radiation, and heating absorption effects, as well as viscous dissipation have been investigated. The model has been represented in a set of partial differential equations and is transformed using suitable similarity transformations which are then solved by using the finite element method through COMSOL.
Keywords: magnetohydrodynamics; nanofluid; velocity; 3D flow; thermal absorption effects; heat absorption effects; shrinking surface